ENGLISH LANGUAGE ACQUISATION OF STUDENTS WITH INTELLECTUAL DISABILITIES AT SPECIAL JUNIOR HIGH SCHOOL IN BENGKULU - Silvia Erlin Sembiring (Edulitics (Education, Literature, and Linguistics) Journal, 2019)
Children with intellectual disabilities are often identified as having limitations in learning languages, however, the variation in the ability to learn English by the children is undeniable. The English language acquirement of the children can be influenced by various factors including educational opportunities which have been regulated in national law. In Indonesia, the national law about Education System No.20/2003 article 5 chapters 1, stated that every citizen has rights to obtain proper education. It means that all citizens have the rights to equal education without exception including children with disabilities, one of whom is children with intellectual disabilities. Intellectual disability is also called congenital cognitive developmental disorder (existing from birth) or cognitive problem that is suffered since childhood. Intellectual disability is also described as several conditions or diagnoses that are different from general characteristics that show disruption in the ability to learn and live in communities. Moreover, in Indonesia, most of children with intellectual disabilities are studying formal education in special schools. In the present time the curriculum in the special school prepares English unit of study that is designed and adapted to the level of abilities and the needs of their students. This research was conducted at a special school, SMPLB Dharma Wanita in Bengkulu Province. The finding showed that there were five levels of acquisition of semantic aspects of students with intellectual disabilities, namely very good, good, sufficient, low and very low. From the fifteen students with intellectual disabilities participants who were observed the average acquisition of their semantic aspects were Low. In addition, the researchers also found that so far the students had learned with learning techniques and textbooks that have been adjusted to the level of their intelligence.